Study of permanent residential management in Tondo Village, Palu City - Salenda, H; Malik, S M; Julia, F; Munawir, Munawir (ASCEE, 2022)
Currently the regional government of Central Sulawesi Province through the Ministry of PUPR has built several permanent residential units (Huntap) for victims of the natural disaster on September 28 2018 that occurred in Palu City, one of which is located in Tondo Village, right behind the Tadulako University Campus. However, based on the results of the initial survey that had been carried out, there were still some things that were not given much attention, such as the provision of housing facilities and infrastructure as well as the shape of houses and their locations that did not respond to the topographic climatic conditions in Palu City. Based on the above premise, regarding the importance of permanent housing arrangement for victims of natural disasters, a problem can be formulated, namely